Optimization of culture conditions of Streptomyces antibioticus strain 1083 to improve the antimicrobial activity against Aeromonas hydrophila - Xuan Canh, Nguyen; Thu Hien, Tran Thi; Thanh Huyen, Nguyen; Anh Minh, Pham Le; Bao Tram, Tran; Thanh Mai, Nguyen Thi (Vietnam Journal of Biotechnology, 2020)
Fish is a healthy, high protein and low fat food that encourages the health and growth of people, especially children. However, in fact fish is very sensitive to many diseases which affects the productivity and quality of fish. Therefore, identifying the cause of the diseases and finding preventive measures become an urgent task today. In the previous study, we isolated Streptomyces antibioticus strain 1083 that has the ability to antagonize Aeromonas hydrophila - a pathogenic bacterium in fish. Based on the obtained results, we continue to perform this study to determine optimal conditions for the culture of S. antibioticus strain 1083 in order to produce antimicrobial compounds against A. hydrophila. The production of antagonists by the strain 1083 was optimized by controlling the condition of different inoculations such as media, pH, temperature and incubation period. The results indicated that International Streptomyces Project 2 (ISP2) was the best medium for S. antibioticus strain 1083 to produce the highest antimicrobial activity against A. hydrophila with 32 mm in diameter of inhibited zone. The actinomycete strain 1083 could express the maximum antimicrobial activity when they were incubated in shaker incubator (200rpm) at 40oC with pH8 in 8 days. The ability of the actinomycete strain in antagonism against A. hydrophila was evaluated by adding different culture medium volume of S. antibioticus strain 1083. With adding 10% cultured solution volume of S. antibioticus strain 1083 into the culture medium of A. hydrophila, after 1 day of inoculation the number of pathogenic bacteria cells were completely eliminated.